34 An investigation of gastrointestinal symptoms, psychological well-being and cognitive performance in informal dementia caregivers. (5th April 2017) - Allen, AP; Chorcorain, A Ní; Wall, J; Cusack, AM; Cryan, JF; Dinan, TG; Kearney, PM; Molloy, DW; Clarke, G
Abstract : Background: Caring for a relative with dementia is considered particularly stressful and is associated with numerous adverse health effects at multiple levels of the brain-gut axis. There is also evidence that long-term family caregivers are more likely to develop irritable bowel syndrome. Aim: The current study aimed to compare family dementia caregivers to a non-caregiver control group, and to examine the impact of interventions, designed to help dementia caregivers manage stress and the caregiving role, on gastrointestinal symptoms, cognitive performance and psychological well-being. Method: Caregiver participants were recruited via clinics at St. Finbarr's Hospital, Cork and control participants via the university community. Participants completed the irritable bowel syndrome symptom severity scale, as well as validated tests of stress, anxiety, and depression. Participants also completed cognitive tasks from the CANTAB battery. A subset of caregivers completed both a carer training program and mindfulness-based stress reduction program. Each program was delivered in a group setting by an experienced instructor and lasted 6-8 weeks. Results: Although caregivers had higher levels of stress and poorer cognitive performance, gastrointestinal symptoms were not altered compared to controls. Following both interventions, caregivers had improved cognitive performance. However, reported stress, anxiety and depression were not significantly altered following the interventions. Stress-reduction interventions also had no significant impact on gastrointestinal function. Conclusions: The stress associated with informal dementia caregivers does not manifest across gastrointestinal symptoms and stress-reduction techniques do not improve gastrointestinal well-being. This is in contrast to the impact of caregiving at higher levels of the brain-gut axis.